ARCUATE FORAMEN OF ATLAS VERTEBRA - b, Senthil Kumar; SELVI G, PANNEER (Innovare Journal of Medical Sciences, 2016)
ABSTRACT The Arcuate foramen is a bony arch which connects the posterior end of the superior articular fossa with the posterior arch of atlas. In case of presence of arcuate foramen the vertebral artery follows the normal course but it has to traverse through the osseo fibrous ring (arcuate foramen). Aim & Objectives To determine the height, width, and area of arcuate foramen and to determine the morphometric difference between the transverse foramen and the canal formed by bony bridges over the vertebral artery of the atlas vertebra. Materials & Methods A total of 75 dry human atlas vertebrae were taken for the study. These vertebrae were examined carefully for the presence of arcuate foramen. Measurements of the maximum dimensions of the arcuate foramen and foramen transversarium were taken. Area of the arcuate foramen was calculated. Differences in dimension of arcuate foramen and foramen transversarium were compared. Side differences of arcuate foramen were compared using the unpaired Student's t test. Results The dimension of arcuate foramen of both sides as compared with dimension of foramen transversarium was found to be more, so the chance of compression of vertebral artery on both sides was less. The percentage of occurrence of arcuate foramen was 2.25% (bilateral) and ponticles was (1.5%) unilateral. Conclusion The dimension of arcuate foramen was more when compared to foramen Transversarium dimensions so the chances of compression of vertebral artery would be less. The knowledge of these foramina may be important for orthopedic surgeons, radiologists, neurosurgeons, and anthropologists. KEYWORDS -Ponticulus Posticus, Arcuate Foramen, Atlas Vertebra, Foramen Transversarium.